Collaborating and interacting: walking together towards our learning community - Carreño Bolivar, Laura Lucia (Colombian Applied Linguistics Journal, 2014)
This article presents the findings of a research study which aimed to explore the collaborative practices of a group of intermediate level students and the way in which students’ interactions contributed to the initial steps towards the establishment of a learning community. Collaboration in this particular study was seen as the actions students took in order to work together towards a common goal. Data revealed that participants went through a three-stage process that moved from individual perspectives to dialogic exchanges to collective constructions of knowledge that emerged from the community they initiated. As students participated in collaborative tasks, they progressively built closer relationships and their sense of belonging to the group progressively increased.